Health Disparities in Otology: A PRISMA‐Based Systematic Review. (7th September 2021) - Lovett, Braeden; Welschmeyer, Alexandra; Johns, James Dixon; Mowry, Sarah; Hoa, Michael
Abstract : Objective: Social determinants of health (SDOHs), including but not limited to sex, race, socioeconomic status, insurance status, and education level, play a significant role in health disparities and affect health outcomes. The purpose of this systematic review is to examine health disparities in otology within the United States and highlight areas warranting further research. Data Sources: PubMed, Ovid MEDLINE. Review Methods: Our search encompassed all years through January 10, 2021. All peer‐reviewed primary literature of any design and publication date regarding health disparities and otology outcomes in the United States was eligible for inclusion. Eligibility assessment was performed via 3 independent investigators. Results: Of the 6326 unique abstracts identified, 188 studies underwent full‐text review, and 52 remained in the final review. The most frequently examined otologic condition was hearing loss (36.5%), followed by cochlear implantation (28.8%) and infection/effusion (15.4%). Vertigo/dizziness (1.9%), Ménière's disease (1.9%), and tinnitus (1.9%) were the least represented otologic conditions. Comprehensive articles on multiple disparity topics were the most common (n = 18), followed by articles on race/ethnicity (n = 11) and socioeconomic status (n = 9). Language (n = 2), education (n = 2), and gender (n = 1) were the least discussed. Over 5‐fold the number of articles were published between 2011 and 2020 compared to the preceding decade (42 vs 8). Conclusion: This study captures the existing literature regarding health disparities and outcomes in otology. The lack of robust data suggests the need for future quality studies aimed at investigating disparities in otologic care, as well as a broader push for recording and reporting SDOHs.